Pesquisa clínica de medicamentos no Brasil: a disposição sobre o próprio corpo como um direito fundamental - Cappello, Thamires Pandolfi (2017)
Clinical research on medicines is a mandatory procedure for pharmaceutical development and registration of new drugs in Brazil. These tests are performed in healthy humans and/or with a certain pathology, in order to verify the possible effects of a substance with therapeutic potential in the human organism. Among its four phases, Phase I is performed with healthy individuals who provide researchers with their bodies, which are analyzed after the administration of substances not yet tested in a human body, through diagnostic tests and other procedures medical-scientific. Therefore, it is verified that the act of disposal of own body for submission to clinical trials of medicines, after free and informed consent, consists of an act based on individual freedom, on the bias of the autonomy of the will, which may, however, endanger the health and physical integrity of the participant. It is noted that several fundamental rights are involved in this area, implying, even, an evident collision to be solved by weighing. It is in this context that the present work is developed with the central objective of verifying that the disposal of own body for clinical research constitutes an individual fundamental right based on the free development of the personality and for the purpose of promoting collective health and national scientific development